Design Research: The Next 500 Years. Issue 1 (4th February 2022) - Hill, Jonathan
In contemporary discourse and practice it is familiar to discuss design research as if it is new to architecture. But this is to ignore the history of the architect. The Architectural Design doctorate is a comparatively new qualification; the first such programme in the United Kingdom was established at the Bartlett School of Architecture, University College London, in the mid-1990s. But the methods and means of design research are not new. Indeed, they have been invaluable to the architect for over 500 years. Studying the history of practice as well as the history of architecture allows us to appreciate that architecture is not made by architects alone. The contemporary relevance of interdisciplinary research, which occurs within, between and across disciplines, indicates that the profession is but one model of practice and implies that others may be more rewarding. In this sense, the architectural design doctorate is a means to investigate and develop alternative models of practice and discourse, acknowledging an interdependent network of diverse – new and old – procedures, not simply because they are useful but because they have social and cultural value.